(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
تم في هذا لبحث الظاهراتي الحصول على علاقة تربط طاقة جسيمة-α بعمر النصف للتفكك الإشعاعي-α لجميع النظائر التي تصدر جسيمات-α، وتؤكد المعطيات التجريبية مدى هذا التعالق الوثيق. كما تم أيضا إيجاد علاقة تربط معدل التفكك الإشعاعي-α بسرعة الضوء، وبالاعتماد على هذه العلاقة الأخيرة وعلى فرضية تزايد سرعة الضوء مع الرجوع في الزمن تم تفسير بعض الظواهر الغامضة المكتشفة حديثا والمتعلقة بتفكك-α الإشعاعي، حيث تم التحقق من أن النشاط الإشعاعي يتزايد مع الرجوع بالزمن، الأمر الذي يفسر الزيادة الكبيرة في جسيمات-α في بعض المواقع على الأرض والتي لا يمكن تفسيرها باستخدام قوانين الإصدار الحالية. In this phenomenological research, a relation connecting α-particle energy and α-decay half-life for all isotopes emitting α-particles have been achieved, and the experimental data affirmed this tight correlation. Also a relation connecting α-decay rate with the speed of light has been established. Depending on this last relation and the hypothesis of increasing light speed as we go back in time, some mysterious phenomena discovered recently, concerning α-decay radioactivity, have also been interpreted. Thus, the increase of radioactivity as we go back in time was proved; which interpreted the enormous amount of α-particles in some positions on the earth that cannot be interpreted using known laws of radioactivity.